Illustrated Guide to the National Electrical Code, 8th Edition - Charles R. Miller (Cengage Learning, 2020)
This uniquely effective guide will help you master the 2020 National Electrical Code®. The author uses highly detailed, technically accurate illustrations to make even the most complex aspects of the code easier to understand and apply, translating the often complicated language of the 2020 NEC® into clear, simple instructions and helpful visuals. Organized logically to make learning easier, the text introduces you to fundamental concepts before progressing to requirements for various dwellings, from one-family homes to multi-family housing, commercial locations and special occupancies. In addition, a convenient, modular format makes it easy to reference relevant information whenever you need it. The Eighth Edition of this trusted resource provides detailed information on key updates and additions to the 2020 NEC, so you can confidently master the industry standards and best practices you'll need to know for career success. With comprehensive coverage, an innovative learning approach and accurate, up-to-date information, this indispensable guide is an ideal resource for students and professionals alike.